Analisis Perbandingan Modul Elektronik dengan Modul Cetak pada Pembelajaran IPS untuk Melihat Indikator Karakter Peduli Lingkungan - Suhara, Yessi Isria; Siska, Nurul Delima; Fadilah, Agus Fadilah; Supriyadi, Muhamad Andri (Journal of Basic Education Research, 2022)
Research Objectives: This study has a purpose, namely to determine the indicators of environmental care characteristics. Where to use this type of quantitative research. Research Methods: The type of research used is quantitative research. The sampling technique used in this study was total sampling and purposive sampling with a total of 18 students. The data analysis used in this research is descriptive and inferential statistics. Main Findings: The results obtained from the significance value of SDS Suria Harapan on the use of printed modules and electronic modules based on local wisdom of ngubat padi, where there is a sig value of 0.605 for the printed module and 0.519 for the electronic module, based on these results it can be said that the data is normally distributed. Novelty of Research: The novelty of this research lies in the electronic module and print module used by researchers which integrate with existing local wisdom so as to improve the character of caring for the environment. While the limitations of this study are that it only focuses on the fifth grade of elementary school